Psychometric evaluation and adaptation of the Spine Oncology Study Group Outcomes Questionnaire to evaluate health‐related quality of life in patients with spinal metastases. Issue 8 (6th February 2018) - Versteeg, Anne L.; Sahgal, Arjun; Rhines, Laurence D.; Sciubba, Daniel M.; Schuster, James M.; Weber, Michael H.; Varga, Peter Pal; Boriani, Stefano; Bettegowda, Chetan; Fehlings, Michael G.; Clarke, Michelle J.; Arnold, Paul M.; et al.
Abstract : BACKGROUND: The Spine Oncology Study Group Outcomes Questionnaire (SOSGOQ) was developed as the first spine oncology‐specific health‐related quality of life (HRQOL) measure. This study evaluated the psychometric properties and clinical validity of the SOSGOQ in a diverse cohort of patients with spinal metastases. METHODS: An international, multicenter, prospective observational cohort study including patients with spinal metastases who underwent surgery and/or radiotherapy was conducted by the AOSpine Knowledge Forum Tumor. Demographic, tumor, and treatment data were collected. HRQOL was evaluated using the SOSGOQ and Medical Outcomes Study Questionnaire Short Form 36 Health Survey (SF‐36) at baseline and fixed follow‐up times. Construct validity was assessed using multitrait scaling analyses, confirmatory factor analyses, and correlation with the SF‐36 and NRS pain score. Test‐retest reliability was assessed in a subgroup of patients between 12 weeks after treatment and the retest 4 to 9 days later. RESULTS: A total of 238 patients were enrolled at 9 centers across North America; 153 of these patients had HRQOL data available at 12 weeks after treatment. Multitrait scaling analyses and confirmatory factor analyses resulted in a refined version of the SOSGOQ with 4 domains and 4 single items. The revised SOSGOQ (SOSGOQ2.0) demonstrated strong correlations with SF‐36 and the ability to discriminate between clinically distinct patient groups. Reliability of the SOSGOQ2.0 was demonstrated to be good, with an intraclass correlation coefficient ranging from 0.58 to 0.92 for the different domains. CONCLUSIONS: The SOSGOQ2.0 is a reliable and valid measure with which to evaluate HRQOL in patients with spinal metastases. It is recommended to use the SOSGOQ2.0 together with a generic HRQOL outcome measure to comprehensively assess HRQOL and increase sensitivity and specificity. Cancer 2018;124:1828‐38 . © 2018 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society. This is an open access article under the terms of the Creative Commons Attribution‐NonCommercial‐NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non‐commercial and no modifications or adaptations are made. Abstract : The revised Spine Oncology Study Group Outcomes Questionnaire (SOSGOQ2.0) is a reliable and valid measure with which to evaluate health‐related quality of life (HRQOL) in patients with spinal metastases. It is recommended to use the SOSGOQ2.0 together with a generic HRQOL outcome measure to comprehensively assess HRQOL and increase sensitivity and specificity.